A label-free photoelectrochemical aptasensor for facile and ultrasensitive mercury ion assay based on a solution-phase photoactive probe and exonuclease III-assisted amplification. Issue 12 (22nd May 2019) - Xu, Ningning; Hou, Ting; Li, Feng
Abstract : An immobilization-free and label-free PEC aptasensing strategy has been developed, with methylene blue in homogeneous solution as a photoactive probe and bare ITO glass as a working electrode and ultrasensitive and highly specific Hg 2+ analysis is successfully achieved. Abstract : In typical photoelectrochemical (PEC) biosensing assays, electrodes are generally modified with photoactive probes and/or target recognition probes, which makes the processes complicated, time-consuming, and difficult to achieve excellent reproducibility. Hence, to overcome such shortcomings, we propose here an immobilization-free and label-free PEC aptasensor using solution-phase methylene blue (MB) as the PEC signal probe. Based on the unique T–Hg 2+ –T base pairs, and the diffusivity difference between free MB molecules and the MB/G-quadruplex composite towards the ITO electrode surface with negative charge, the "signal-off" approach for Hg 2+ detection is developed. In the presence of target Hg 2+, via the T–Hg 2+ –T bond formation, the two sticky ends of the hairpin DNA probe form a rigid duplex stem, which triggers the exonuclease III-facilitated target cycling amplification, and the formation of multiple G-quadruplexes. Upon the intercalation of MB in G-quadruplexes, significantly decreased photocurrent is obtained owing to the increased electrostatic repulsion between the MB/G-quadruplex composite and the ITO electrode. Therefore, highly sensitive and ultrasensitive Hg 2+ determination is achieved, with a low detection limit of 1.2 pM, well below the maximum allowable Hg 2+ level in drinking water defined by the WHO, China's Ministry of Health, and the US EPA. Due to the avoidance of sophisticated electrode modification and recognition probe immobilization processes, as well as an expensive labeling procedure, the PEC aptasensor proposed here demonstrates the advantages of simplicity, good reproducibility, rapidness and low cost.